Fashion, Image, and Consumerism: fashion editorials as a communication strategy for brands (ModaPalavra e-periódico, 2020)
This article aimed to address the theme of fashion editorials as a communication strategy and consumption for brands. Brings a general overview on consumption and fashion communication, as well as an explanation of what are editorials, how these are made and for what they serve. This article was based on the bibliography of several authors in order to clarify the area and the communicative potential of editorials for fashion brands.
Keywords: fashion editoria; image; communication; consumption